Analysis of the Application of Accounting and Income Tax Provisions on Debt Write-Offs in the Homologation of Suspension of Debt Payment Obligations in Accordance with PSAK 109 - Zakky Ashidiqi (LP2M IAIN Palopo, 2026)
This study investigates the application of accounting and income tax provisions on debt write-offs in the homologation of Suspension of Debt Payment Obligations (PKPU) in Indonesia, a phenomenon that has intensified since the Covid-19 pandemic. The research aims to analyze the implications of PSAK 109 and tax regulations on debt restructuring, providing practical guidance for companies. Employing a qualitative case study approach, data were collected through in-depth interviews with tax authorities, practitioners, and academics, as well as document analysis. The population includes all stakeholders in PKPU homologation, with purposive sampling focusing on those with direct experience in PSAK 109 implementation. Thematic coding was used for data analysis. The results show that only realized gains from debt reduction (haircut) are recognized as taxable income, while unrealized gains are not immediately taxed. The study concludes that clear regulatory guidelines are needed to minimize disputes and support compliance. The findings highlight the necessity for adaptive policies in post-pandemic debt restructuring.